A pooled mean group estimation on ICT infrastructure and economic growth in ASEAN-5 countries - Mohd Mahyideen, Jamilah; Ismail, Normaz Wana; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study empirically investigates the effects of infrastructures for information and communications technologies (ICT) on economic growth in selected ASEAN countries over the period 1980–2010. The studies of ICT infrastructure have received much attention in recent literature for its potential contribution towards growth and productivity. However, there is little empirical evidence on the effects of ICT infrastructure on growth performance, particularly for ASEAN countries. This study examines recent data using the pooled mean group estimator (PMGE). The availability of ICT infrastructure is captured by the number of subscriptions for both fixed line and mobile phone, the number of telephone lines, the number of mobile cellular subscriptions and the number of internet users. Empirical results show statistically significant positive correlations for all four variables. This study concludes that ICT infrastructure is a key driver of ASEAN economic growth.